2011
DOI: 10.1007/s10734-011-9426-y
|View full text |Cite
|
Sign up to set email alerts
|

Good practice for enhancing the engagement and success of commencing students

Abstract: There is widespread recognition that higher education institutions (HEIs) must actively support commencing students to ensure equity in access to the opportunities afforded by higher education. This role is particularly critical for students who because of educational, cultural or financial disadvantage or because they are members of social groups currently under-represented in higher education, may require additional transitional support to ''level the playing field.'' The challenge faced by HEIs is to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 4 publications
2
52
0
9
Order By: Relevance
“…UK universities have responded to the risks associated with the transition to university, by providing high levels of structured support for students in their first year to try to ensure that they make friends, feel supported by staff and settle into their new environment (Nelson, Quinn, Marrington, & Clarke, 2012). The data here suggest that this may be helpful in aiding student adjustment at the transition and promoting their well-being given that levels of psychological symptoms do not increase over the first six months of university attendance.…”
Section: University Student Mental Health 14mentioning
confidence: 87%
“…UK universities have responded to the risks associated with the transition to university, by providing high levels of structured support for students in their first year to try to ensure that they make friends, feel supported by staff and settle into their new environment (Nelson, Quinn, Marrington, & Clarke, 2012). The data here suggest that this may be helpful in aiding student adjustment at the transition and promoting their well-being given that levels of psychological symptoms do not increase over the first six months of university attendance.…”
Section: University Student Mental Health 14mentioning
confidence: 87%
“…For example, a study of 1197 students from a UK university (Macaskill, 2013) 20 found highest levels of psychiatric symptoms in second-year students. It was argued that 21 while UK universities targeted additional support for first-year students to enable a smoother 22 transition to university life (Nelson et al, 2013), the second year of study comprises a While some students experience psychological disturbance during time at university, 7 many others cope effectively and some thrive amidst the challenges. Whether someone 8 becomes mentally ill or functions optimally when faced with challenging circumstances is 9 likely due to complex interactions between genetic, biological, social, and cultural factors.…”
mentioning
confidence: 99%
“…Gilmore Gilmour (2014) reported that 20 per cent of Australian students leave university in their first year. It is widely argued that such attrition rates are primarily the result of student disengagement with their studies, peers and institutions (Barron & D'Annunzio-Green, 2009;Cornelius, Wood, & Lai, 2016;Nelson, Quinn, Marrington, & Clarke, 2012). Peer mentoring programs have attempted to reverse this attrition rate and increase student engagement by providing programs that offer strong interpersonal and academic support.…”
Section: Introductionmentioning
confidence: 99%